Analysis On Code-Switching Encountered in The Conversation of Daniel Mananta and His Guest Stars on “Daniel Tetangga Kamu” Video Youtube Channel - Nitiyas, Rita; Sri Rezeki, Yanti; Wardah (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study aims to describe the type of code-switching encountered in the conversation of Daniel Mananta and his guest stars on “Daniel Tetangga Kamu” video Youtube channel. This research covered three types of code-switching as a discussion for further linguistic study on code-switching. A descriptive qualitative method is used for this study to analyze the data collected from three videos out of the videos uploaded of Daniel Mananta in youtube. The method is applied to give a clear description of the data according to the three types of code-switching by Poplack. Then, the data were sorted out of the selected corpora from video transcription. The result of this analysis showed that there were types of code-switching found in this conversation, including inter-sentential switching, intra-sentential switching, and tag switching. Type of code-switching which is intra-sentential was the most frequently encountered in corpora with 111 data.